Resident of Kandivli Gaothan - Mumbai Archive Project Team (Jio Institute, 2024)
Ramnath Damodar Keny, a 70-year-old inhabitant of Kandivli village, has spent his entire life in this locality. Five generations of his family have lived in the same house.